Thermal Transport in Polyethylene: The Effect of Force Fields and Crystallinity - Sæther, Sandra; Falck, Merete; Zhang, Zhiliang; Lervik, Anders; He, Jianying (Macromolecules, 2021)
In this article, we study the local structure and heat transfer properties (thermal conductivity and interfacial conductance) in model semi-crystalline polyethylene (PE) by non-equilibrium molecular dynamics. We compare three different force fields with different levels of detail (all-atom, all-atom with constraints, and united-atom) and find that the structure of the model PE is significantly influenced by the choice of force field. The united-atom force field results in a reduced overall crystallinity and an over-idealized organization of the polymer chains, compared to the all-atom force fields. We find that thermal transport properties are not greatly influenced when structural effects are taken into consideration, and our results suggest that united-atom models can be used to study heat transfer properties of model PE, with decreased computational cost.